Multiplicación in vitro del anturio blanco anthurium andreanum utilizando diferentes medios de cultivo - Ramírez Macharé, Roxana Morayma (2012)
In the biotechnology laboratory of the Postgraduate School of the Faculty of Agricultural Sciences at the Technical University of Machala, we performed investigation to propagate in vitro conditions of export ornamental plants of the genus Anthurium, which raised the following objectives "to determine the best treatment of cultivation medium for in vitro multiplication of white Anthurium (Anthurium andraeanum) Establish and costs required in vitro multiplication of white Anthurium (Anthurium andraeanum). To meet the proposed objectives were counted with the laboratory, laminar flow hood, stoves, microscope, autoclave and materials: 1 box of surgical gloves, 1 liter of liquid soap, 1 gallon of industrial alcohol, 1 box of masks, 1 pack of cotton wool, aluminum foil, sterilize covers high density, 1 pound of sugar, agar, maskingtake, parafilm, chlorine, detergent, disinfectant floor, sponge, mop, distilled water plants, wash bottles, 1 box # 22 scalpel blades. The treatments consisted of six in number T1. BAP: 1.0 mg; T2. ANA: 0, 05 mg; T3. BAP+ANA: 1 mg+0, 05 mg; T4. BAP +ANA: 1, 5 mg +0, 01 mg; T5. BAP +ANA: 1, 5 mg + 0, 05 mg; T6. BAP: 1, 5 mg. The variables studied were, number of shoots, shoot length and number of leaves. Treatments were arranged according to a completely randomized design with six treatments and five repetitions, totaling 30 experimental units. The unit's integrated Experimental 5 bottles with 1 explant mothers Anthurium plants were selected from a roster outbreaks vitro mother plants, which were managed with a disinfection protocol solutions Kasumil 4 ml / liter sodium hydroxide (5.25% ai). Between each step be conducted 3 rinses with sterile distilled water. The cultivation medium will comprise salts of Murashige and Skoog 100% sucrose and 30 mg / l in the multiplication phase. In the analysis of the variables analyzed did not obtain statistical significance for treatment, and no significant differences between the means of treatments, also recorded high variability between experimental units and between treatments, which was due to mortality of explants due to phenolization vitro plants of the The benzylaminopurine BAP 1.0 and 1.5 mg naphthaleneacetic acid and 0.05 to 0.1 mg ANA did not influence the different variables evaluated to test the hypothesis of the goodness of their effects on in vitro propagation of the Anthurium andreanum. The sterility of the laboratory was negative for the purposes of making a bulked propagation. Q The treatments included two phytohormones BAP and ANA were not efficient in enhancing regenerative capacity of meristematic cells that lead to the formation of new shoots and roots and the money invested contos for 25 plants in optimal conditions varied between 66.24 to $ 69.62, corresponding to a unit value of $ 2.65 to $ 2.72 per plant.